Resident Surgical Training in Glaucoma - Gedde, Steven J. (Curr Opin Ophthalmol, 2016)
PURPOSE OF REVIEW: This review provides an overview of the training of ophthalmology residents to perform glaucoma surgery. RECENT FINDINGS: Data from the Accreditation Council for Graduate Medical Education indicate that the average number of glaucoma surgeries performed by graduating ophthalmology residents has remained stable over the past 5 years. However, a proportional increase in shunting procedures and decrease in filtering procedures has occurred during this time period. The existing medical literature has not identified any differences in the safety and efficacy of glaucoma procedures performed by residents compared with those performed by glaucoma specialists. A structured curriculum for glaucoma is designed to help residents transition from the wet lab to live surgery, and it serves to maximize resident learning and patient safety. SUMMARY: Tube shunts are being used with greater frequency in the surgical management of glaucoma as an alternative to trabeculectomy, and this shift in practice patterns is reflected in the surgical experience of ophthalmology residents. Patients should be reassured by the outcomes of resident-performed glaucoma surgery, which compare favorably with those reported by experienced glaucoma surgeons. A structured curriculum can assist in introducing residents to glaucoma surgery.